The politics of hero myth in President Jokowi's biopic film (2013) - Muhammad Dzaky Abdullah; Ari J. Adipurwawidjana; Muhamad Adji (Satwika : Kajian Ilmu Budaya dan Perubahan Sosial, 2025)
Among the prominent Indonesian biographical films concerning "national heroes" that emerged in the 2010s is "Jokowi" (2013). This film narrates the life of Joko Widodo (Jokowi), who was then serving as the Governor of Jakarta and was released a month prior to the announcement of his presidential candidacy in the 2014 elections. The film predominantly focuses on Jokowi's personal life, including his romantic experiences, rather than his political career. This emphasis underscores the significance of personal character construction in creating a leader's myth in Indonesia. Employing the methodologies of film narratology and mythological semiotics, this article examines how the film, through its scenes, plot, and characterization, constructs a myth of Jokowi that bolsters his image as a political leader. The depiction of Jokowi as a masculine, family oriented, and decisive leader presents him as an "ideal" character. This article posits that such portrayal endeavors to integrate the character into the cultural mythology as a "hero." The film's narrative, which follows a heroic pattern and aligns the character with Javanese wayang heroes, positions Jokowi as a classical hero. The marketing of the biopic as a "true story" carries political implications, specifically for the 2014 election and Jokowi's image, and more broadly for the ideological discourse of the state, particularly Bapakism and the paternal function of the state.   Di antara film arus utama Indonesia bergenre biopik mengenai “pahlawan nasional” yang muncul pada dekade 2010, terdapat film Jokowi (2013). Film ini mengangkat kisah hidup Joko Widodo (Jokowi), yang pada waktu itu adalah Gubernur DKI Jakarta, dan dirilis sebulan sebelum pengumuman pencalonannya sebagai presiden pada pemilu 2014. Film ini berfokus pada kisah kehidupan pribadi Jokowi seperti pada aspek romansanya dan bukan pada perjalanan politiknya. Hal ini menunjukkan bahwa konstruksi pribadi tokoh merupakan bagian penting dalam penciptaan mitos seorang pemimpin di Indonesia. Menggunakan pendekatan naratologi film dan semiotika mitologi, artikel ini menelusuri cara film melalui adegan-adegan, plot, dan karakterisasi melakukan pembangunan mitos pada tokoh Jokowi yang mendukung Jokowi sebagai tokoh politik. Penggambaran tokoh Jokowi dalam film sebagai laki-laki maskulin, family man, dan pemimpin tegas mempresentasikan tokoh sebagai “ideal”. Artikel ini berargumen bahwa hal tersebut merupakan usaha untuk menyuntikkan tokoh pada kumpulan mitologi kultural sebagai seorang “hero”. Naratif film yang memiliki pola heroik dan penyandingan tokoh dengan pahlawan wayang Jawa mengonstruksi Jokowi sebagai seorang hero klasik. Pemasaran biopik sebagai “kisah nyata” memiliki implikasi politis: untuk kepentingan pemilihan umum 2014 dan citra Jokowi secara spesifik,  dan untuk wacana ideologis negara, yakni Bapakisme dan fungsi paternal negara, secara umum.